Direct current electrical fields inhibit cancer cell motility in microchannel confinements - Benjamin Karem Naggay; Saeed Khomeijani Farahani; Xu Gao; Andrew Holle; Ralf Kemkemer (Scientific Reports)
Abstract The capability of cells to sense and respond to endogenous electrical fields plays a crucial role in processes like nerve regeneration, wound healing, and development. In vitro, many cell types respond to electrical fields by migrating along the corresponding electrical field vectors. This process is known as galvano- or electrotaxis. Here we report on the combined impact of micro-confinements and direct current electrical fields (dcEFs) on the motility of MDA-MB-231 human breast cancer cells using a self-developed, easy-to-use platform with microchannels ranging from 3  $$\upmu$$ μ m to 11  $$\upmu$$ μ m in width and 11  $$\upmu$$ μ m height. We found that MDA-MB-231 cells respond to exogenous electrical fields ranging from 100 mV mm $$^{-1}$$ - 1 to 1000 mV mm $$^{-1}$$ - 1 with altered cell motility depending on the confinement size. Our data show an overall inhibited galvanotaxis in confinements, while in contrast an enhancing effect in unconfined galvanotaxis is found. The application of direct current electrical fields to microchannels not only caused a reduction in migration speed but also decreased the number of permeating cells. By applying 1000 mV mm $$^{-1}$$ - 1 , single-cell permeation could be prevented in confinements of 5  $$\upmu$$ μ m and smaller.